1999
DOI: 10.1002/(sici)1098-2345(1999)47:2<133::aid-ajp4>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variation in the calls of wild chimpanzees: A reassessment

Abstract: Male chimpanzees produce a species‐typical call, the pant hoot, to communicate to conspecifics over long‐distances. Calls given by males from the well‐known Gombe and Mahale populations typically consist of four different phases: an introduction, build‐up, climax, and let‐down. Recent observations suggest that chimpanzees living in the Kibale National Park, Uganda, consistently give calls that lack a build‐up and are thus qualitatively distinguishable acoustically from those made by other East African conspeci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
97
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(113 citation statements)
references
References 49 publications
14
97
2
Order By: Relevance
“…For example, early papers on geographical variation in pant hoots of chimpanzees (Pan troglodytes) suggested that this variation was evidence for production learning in this species (Mitani et al 1992;Mitani and Brandt 1994;Clark Arcadi 1996). Mitani et al (1999) reassessed the interpretation of geographical variation in chimpanzee calls. They concluded "The preceding observations suggest that genetically based rather than cultural [sensu McGrew, 1992] differences are likely to underlie any vocal variations that exist between Mahale and Kibale chimpanzees."…”
Section: Geographical and Temporal Variation In Callssupporting
confidence: 80%
“…For example, early papers on geographical variation in pant hoots of chimpanzees (Pan troglodytes) suggested that this variation was evidence for production learning in this species (Mitani et al 1992;Mitani and Brandt 1994;Clark Arcadi 1996). Mitani et al (1999) reassessed the interpretation of geographical variation in chimpanzee calls. They concluded "The preceding observations suggest that genetically based rather than cultural [sensu McGrew, 1992] differences are likely to underlie any vocal variations that exist between Mahale and Kibale chimpanzees."…”
Section: Geographical and Temporal Variation In Callssupporting
confidence: 80%
“…Of course, this relative loss does not mean that chimpanzees cannot hear in the midrange frequencies, but rather that they are adapted to hear best at Ϸ1 kHz and 8 kHz. It is interesting to note that the species-specific pant-hoots regularly emitted by wild chimpanzees to communicate with conspecifics over long distances concentrate the acoustic information at Ϸ1 kHz (10).…”
mentioning
confidence: 99%
“…van Hooff, 1971, van Hooff, 1967, Parr et al, 2007, Parr et al, 2002, Marler and Tenaza, 1977, Marler and Hobbett, 1975, Marler, 1969, Mitani et al, 1999. Repertoire of manual gestural communication in chimpanzees to date received limited research attention and has been studied within broader framework of the whole gesture repertoire focusing on all communicative bodily movements.…”
Section: Aims Of the Studymentioning
confidence: 99%
“…In addition, the gestural repertoire size identified here is similar to the repertoire size van Hooff, 1971, van Hooff, 1967, Parr et al, 2007, Marler and Tenaza, 1977, Marler and Hobbett, 1975, Marler, 1969, Mitani et al, 1999. with both the complexity of the social system and the complexity of cognitive skills in primates (see also Aiello and Dunbar, 1993, Dunbar, 1998, Dunbar, 1993, Dunbar, 1996.…”
Section: Katja Liebal 2004mentioning
confidence: 99%